A sustentabilidade sob a ótica da moda: uma leitura acerca do papel da informação ambiental - COSTA, Alessa Caroline Prazeres da (2017)
A reflection on sustainability from the point of view of fashion presenting environmental information as a relevant resource for this frame, with the purpose of analyzing the informational context that leads it towards transformation in contemporary society. The analysis consisted of an exploratory study based on bibliographic research with a qualitative approach, in which results emphasized fashion as an influential agent in intentions, actions and the strengthening of sustainability and its implications in the reality of the environmental issue, which is not restricted to a single process, but to a wide reach, affecting different fields, such as the society itself, recognizing, in this process, environmental information as a subsidy for sustainable fashion, considering its compounding elements, established by the aid of environmental education. The conclusion is that fashion, as a time reflection, is sustained by the desires of the outside world and depicts its influences, as well as it shows itself and acts on it, both observed in sustainable fashion, which, in addition to representing the environmental information, can also use it as a tool for its own purposes.